Dentin bond strength: Influence of laser irradiation, acid etching, and hypermineralization - Goncalves, SED; De Araujo, MAM; Demiao, A. J. (Mary Ann Liebert, Inc., 1999)
Objective: the purpose of the present study was to investigate the effects of ND:YLF laser irradiation (1.31 J/cm(2); 250 mJ per pulse), acid etching, and hypermineralization on the shear bond strength (SBS) of the Scotchbond Multi-Purpose Plus (3M Dental Products) bonding system. Summary Background Data: Previous studies had shown that the pretreatment of the dentin substrate with laser irradiation can influence the SBS, Methods: Sixty bovine incisors were selected and stored at -18 degrees C, Dentinal buccal surface was exposed and radiographs were taken to control dentin thickness, the specimens were separated into 2 groups: (1) the control, which was kept in distilled water at 4 degrees C; (2) the hypermineralized, which was kept in hypermineralizing solution at 4 degrees C for 14 days, Each group was divided into 3 subgroups according to the type of dentin pretreatment used: M (acid etching + primer + bond); AL (acid etching + primer + bond + laser); and LA (laser + acid etching + primer + bond). A standard composite resin cylinder (Z100-3M) was bonded to the dentinal surface and the SBS performed on an Instron machine (500 Kg load cell at 0.5 mm/min), followed by scanning electron microscopy (SEM) and x-ray diffraction analysis. Results: Analysis of variance (ANOVA) determined that the pretreatments influenced the SBS values (p < 0.05): AL (9.96 MPa), M (7.28 MPa), and LA (4.87 MPa), the interaction between the group and pretreatment factors also influenced the SBS (p < 0.05). The highest values were obtained for the interaction control/AL (11.64 MPa), Conclusion: the results suggested that dentin treatment with laser after the application of the adhesive system is efficient in achieving higher bond strength and is promising as a possible new adhesive substrate.